Construção de ontologias de tarefa e sua reutilização na engenharia de requisitos - Martins, Aline Freitas (2009)
Nowadays, it is acknowledged that reuse offers an important opportunity to achieve improvements in software development. Greater benefits, however, are achieved by reusing knowledge. Concerning knowledge reuse, two major kinds of knowledge should be considered: domain and task knowledge. For developing knowledge for reuse, models are needed to capture both, and ontologies can be used for this purpose. Domain ontologies describe the vocabulary related to a generic domain, while task ontologies describe the vocabulary related to a generic task. Domain ontologies have been extensively used in several areas in Computer Science, however, the same does not occur with task ontologies. There are few works presenting task ontologies, and there is no uniformity in representing them. Task knowledge involves two different facets: task decomposition and knowledge roles involved in the fulfillment of the subtasks. This work proposes the use of UFO (Unified Foundational Ontology) based UML profiles for representing task knowledge: OntoUML (that concerns class diagrams) modeling the knowledge roles involved and their properties and relations, and E-OntoUML (that concerns activity diagrams) capturing task decomposition and how knowledge roles act in their fulfillment. OntoUML is currently used to represent several domain ontologies. E-OntoUML is a new profile that is proposed here. This work also discusses how task ontologies can be combined with domain ontologies in order to describe the knowledge involved in a class of applications. Finally, since the main goal for capturing knowledge is to allow its reuse and sharing, an approach is proposed for reusing task ontologies in the Requirements Engineering process.